Simplify the following boolean expression, using four-variable maps:
A' B' C' D' + A'CD' + AB'D'+ABCD + A' BD
The expression is: A' B' C' D' + A'CD' + AB'D'+ABCD + A' BD
We can begin by expanding it as follows:
A′B(CD′+D)+B(C+A′BD)A′B(CD′+D)+B(C+A′BD)
=A′B(C+D)+B(C+A′BD)(∵x+x′y=x+y)=A′B(C+D)+B(C+A′BD)(∵x+x′y=x+y)
=A′BC+A′BD+BC+A′BD)(∵xx=x)=A′BC+A′BD+BC+A′BD)(∵xx=x)
=A′BC+BC+A′BD(∵x+x=x)=A′BC+BC+A′BD(∵x+x=x)
=BC(A′+1)+A′BD=BC(A′+1)+A′BD
=BC+A′BD(∵1+x=1)
Our map is represented as follows:
Comments
Leave a comment